La campagna del Henares : (Cantar de Miocid, lasse 19-26) (Carte Romanze, 2022)
As part of his work on a new edition of Cantar de mio Cid, the author presents a sample of the verses 285-294 and 404-556 of the poem in a twofold synoptic version, with an interpretative text and a critical reconstruction. The first is true to the single manuscript and only corrects the copyist’s mistakes. The latter is based on the metric theory that was explained by the author in other essays, enriched by the resort to indirect tradition, usus scribendi, conformatio textus and the plot’s inner logic. The text is accompanied by philological notes.